Citation Resources of Higher Education Students: A Contrast Between Academic Papers and Facebook Posts (2018)
Currently, there is a dissociation between the vernacular activity carried out by the student in his social life and the activity of the classroom. Given that in this social life the virtual field is becoming more and more important, the analysis of posts on Facebook and of academic texts of students of the bachelor’s program in Foreign Languages of the Universidad del Valle is proposed. Specifically, we focus on the mechanisms used by the students to introduce a direct textual citation in the case of the academic paper, and a link, an image or a video (when it is not theirs) in the case of the social network. The main objective is to establish a contrast between the citation resources in the scholarly and virtual fields. This qualitative study is descriptive in nature, which allows us to provide a general overview of these students' citation management, and their influence on the construction of disciplinary knowledge. The analysis of the data shows shortcomings in the scholarly management of information and communication technologies (ICT), since it is broadly observed that students appropriate digital content as if it were colloquial speech, without paying attention to its authorship, reliability or provenance, and ignore basic aspects of their reuse in scholarly contexts, such as citation or established scholarly conventions. Finally, it is considered pertinent to describe the resources of the new digital writings, in order to carry out a complete characterization and propose didactic actions to address scholarly writing and its relationship with the internet.